Legal Consequences of Implementing Ijarah Contracts in Sukuk Issuance - Sisi Ade Linda; Iwan Setiawan; Muhamad Izazi Nurjaman (Qawanin: Jurnal of Economic Syaria Law, 2023)
Currently, the development of the Islamic capital market shows rapid progress, as evidenced by the increase in the index in the JII (Jakarta Islamic Index) list. The presence of Islamic financial products such as sharia invests is considered to be a solution to investment problems that have occurred recently. One of the islamic financial products that is developing today is sukuk. Today sukuk has become one of the strongest elements in the Islamic economy. one type of sukuk in Indonesia is the ijarah sukuk. The research method used in this study is a qualitative method with a descriptive approach, which collects data related to sukuk in the ijarah contract taken from sources such as books, journals, skrpisi, thesis, and other related sources. The results showed that the Ijarah sukuk is a type of letter that indicates an ownership of an asset, for which the asset is leased. This sukuk is one type of letter that can be traded because the sukuk gives the right to the holders to get money from the lease proceeds as well as the right to transfer ownership without any taking rights from the tenant.